Yale observational score (YOS) to detect serious bacterial infections in young febrile children (Panacea Journal of Medical Sciences, 2022)
Introduction: Fever is one of the common presentation of children to paediatric emergency. Fever is defined as axillary temperature of ? 99.5 °F. A young febrile child without definite localizing sign of infection may develop bacteraemia and serious bacterial infection (SBI) leading to fatal outcome. Hence, an early diagnosis of SBI in a febrile child is crucial to reduce childhood mortality. Yale observation scale utilizes some simple clinical parameters to predict serious bacterial infection in young children.Hence this study is undertaken to test the utility of YOS in predicting serious bacterial infection in small children so as to investigate them in time and start treatment early to prevent complications.Materials and Methods: 150 consecutive children 1-36 months of age with axillary temperature>99.5 ?F were enrolled and YOS scoring assigned to each of them. This was followed by physical examination and extensive laboratory testing with CBC, Urine and routine microscopy, chest x-ray, CRP, blood and urine cultures.Results: In patients with SBI, the YOS of ?10 was observed in only 9.23% (6/65) of patients compared to 48.24% (41/85) of patients without SBI. There was a significantly high YOS i.e. >10 in patients diagnosed with SBI (? =24.26; P  Results: Mean temperature elevation, higher values of TLC, ANC and CRP positivity results in higher YOS scoring and more chance to have serious bacterial infection.Conclusion: YOS score is very useful in ruling out serious bacterial infection in 1-36 months age group at cut-off value of 12. Significantly higher scores (>16) depict essentially serious bacterial infection and poorer outcome.